A Child with Roberts Syndrome: A Case Report - Sharma, Rajan K; Sharma, Gopal R; Bista, Prakash; Jha, Rajiv (Nepal Journal of Neuroscience, 2017)
Roberts syndrome is a genetically determined rare birth defect causing, skeletal deformities, particularly symmetrical limb reduction and craniofacial anomalies. For any child with limb and craniofacial bony malformations, this syndrome should be considered in the differentials. Although this syndrome represents only a small proportion of the total number of individuals with limb defi ciency, it is important to be identified in order to give accurate genetic counseling including recurrence risk in siblings and possible prenatal diagnosis. This is the case report of a 9 year old female child who presented with defective development of all four extremities and craniofacial abnormalities. The overall clinical and radiological features were suggestive of Roberts syndrome. Nepal Journal of Neuroscience, Vol. 14, No. 2, 2017 Page: 39-42